Impact and Failure of Internal Pressure of Pipe Connections C Influenced by Sea Water - Firman Husain (Collaborate Engineering Daily Book Series, 2023)
The consequences of seawater absorption on the impact behaviour of glass/epoxy composite elbow pipe joints were investigated experimentally. Glass-epoxy elbow pipe connections using E-glass and S-glass are made using hand layup. Pipe connections are soaked in water according to current conditions for 0,3 and 6 months. The relationship between unmanaged and aged samples was studied by calculating contact force, displacement, and absorbed energy values ​​from impact tests. Therefore, it is concluded that seawater increases the ageing period of E-glass/epoxy fibre-reinforced composite pipe elbow joints, resulting in degradation between the fibre and resin interface, which is more prominent in elbow joints made with E-glass than in those made with S-fiber—proposed glass.